Juridical Analysis: Unraveling Malaysia’s Modification of the Song ”˜Halo-Halo Bandung’ Within the Legal Parameters of Law No. 24 of 2014 - Halim, Tobyas; Harsha, Ravano; Sinurat, Gogo (Anthology: Inside Intellectual Property Rights, 2024)
Copyright in particular is an essential component of intellectual property rights, which are necessary to protect artistic creations and acknowledge author ownership. These rights provide writers complete control over their works, guaranteeing that they are properly credited and compensated for their contributions. Malaysia misrepresented the song "Halo-halo Bandung" as "Hello Kuala Lumpur," falsely claiming it to be a Malaysian anthem despite its obvious similarities to the original Indonesian composition by Ismail Marzuki. This is an example that emphasizes the significance of this allegation. This misattribution is against copyright laws, demonstrating a disregard for the integrity of intellectual property and creative boundaries. Article 40 within the framework of Law No. 28 of 2014 regarding Copyright explicitly identifies musical compositions as a specific form of creative work entitled to protection under copyright law. The study aims to detail and demonstrate how Malaysia misinterpreted the song “Halo-Halo Bandung” in contravention of Copyright Law. This serves to exemplify Indonesia’s endeavors as a member of the World Trade Organization in addressing Malaysia’s infringement of the song’s copyright. In order to prevent such infringements and maintain the originality of creative expression, this thesis highlights the need of maintaining copyright rights and the necessity of international cooperation.